(untitled) (Journal of the College of Basic Education, 2022)
An analytical study aimed at diagnosing indicators of weakness in master’s theses in the faculties of universities in Baghdad province, and it adopted the descriptive analytical approach. A composite questionnaire was built consisting of three parts, the first part included paragraphs on indicators of weakness, the second part included paragraphs about the causes of weakness, and the third part included paragraphs about treatments and proposals, and it included (163) items. The questionnaire, in its three parts, was presented to (25) experts using the Delphi method, and an agreement rate of 80% was approved. The questionnaire was applied in the second semester of the academic year 2014-2015. Its validity and reliability were confirmed. It was analyzed using percentages and discussing its fields according to the following: First, analysis and discussion of weakness indicators in its six areas (indicators of general weakness in messages, indicators of weakness in organization and output